THE ROLE OF ACCOUNTING RECORD-KEEPING IN IMPROVING ACCESS TO SME FINANCING - Marina Marina (Adisam Publisher, 2026)
Micro, small, and medium enterprises (MSMEs) play a strategic role in the economy, but still face major obstacles in obtaining access to financing from financial institutions. One factor contributing to this limitation is the poor quality of accounting records kept by MSME operators. This study aims to analyse the role of accounting records in improving MSME access to financing. The research method used is a qualitative approach with data collection techniques through interviews, observation, and documentation of MSME actors. The results show that good accounting records can increase transparency, accountability, and business credibility, thereby making it easier for MSMEs to meet financing requirements. Systematically compiled financial reports help business actors understand their financial condition, manage cash flow, and provide a basis for financial institutions to consider granting credit. In addition, the implementation of simple accounting records has been proven to increase the confidence of banks and financing institutions in the feasibility of MSME businesses. The implications of this research confirm that improving accounting literacy and providing financial record-keeping assistance to MSMEs are important factors in expanding access to financing. Therefore, support from the government, financial institutions, and business mentors is needed to encourage the implementation of effective and sustainable accounting practices in MSMEs.